Examining Factors Impacting Online Survey Response Rates in Educational Research: Perceptions of Graduate Students - Amany Saleh; Krishna Bista (Journal of MultiDisciplinary Evaluation)
Background: In educational research, online survey has become one of the most popular methods of data collection. Academic researchers, including faculty and students, expect and require a good response rate to their research projects for reliable results.